Advances in applied microbiology. - Laskin, Allen I., 1928-; Bennett, J. W.; Gadd, Geoffrey M. (Advances in applied microbiology, 2003)
An eclectic volume of topical reviews on all aspects of applied microbiology. It contains 14 comprehensive reviews of current research in applied microbiology. * Discusses soil based gene discovery * Review deticated to microbial phosphate removal and plyphosphate production from wastewaters * Covers acid resistance in E. coli.